Initial Bat Surveillance in Lampung: Uncovering the Potential Reservoir of Coronaviruses and Zoonotic Disease Risks - Elly Lestari Rustiati; Priyambodo Priyambodo; Azmi Sevira Nur; Neli Pratiwi; Nova Yunior; Kurniasih Vidyanti; Saswiyanti Enny; Master Jani; Eko Srihanto (BIOVALENTIA: Biological Research Journal, 2026)
Bats are recognized as ecologically important mammals and potential natural reservoirs of zoonotic pathogens, including coronaviruses. However, baseline ecological information on bat diversity in human-influenced landscapes of Lampung, Indonesia, remains limited. This study aimed to conduct initial surveillance of bat diversity in selected urban and rural habitats in Lampung and to provide an ecological basis for assessing potential zoonotic risk contexts. Bat sampling was conducted using mist net trapping in four locations representing urban and rural landscapes, followed by morphological and morphometric identification. A total of 37 individuals representing five bat species were recorded, comprising four fruit-eating species, Cynopterus brachyotis, Cynopterus sphinx, Cynopterus horsfieldii, and Cynopterus titthaecheilus, and one insectivorous species, Scotophilus kuhlii. The predominance of C. brachyotis across all sites indicates broad ecological adaptability, particularly in human-modified environments. Rural habitats supported greater species representation than urban sites, suggesting the influence of habitat heterogeneity on bat assemblages. Morphometric and reproductive observations further supported species discrimination and ecological interpretation. Although this study did not assess pathogen presence directly, the occurrence of bats at human–wildlife interfaces provides important baseline information for future surveillance related to reservoir hosts and zoonotic disease risks. These findings contribute to understanding bat diversity in Lampung and support further ecological and epidemiological investigations.